Analisis Proses Bisnis Sistem Informasi Administrasi Kependudukan (SIAK) Menggunakan Business Process Modelling Notation (BPMN) - Tomu, Irwanto Is.; Djeden, Fajriyanto; Setiawan, Edi; Sukmawati, Iren (Gorontalo State University, 2024)
The Department of Population and Civil Registration of Bone Bolango Regency is a regional organization that carries out government affairs in the administration field in the form of issuing KTP-E, KK, Birth/Death Certificates, Child Identity Cards and other population information such as moving in, changing addresses and changing status. The Business Process Modeling Notation (BPMN) method describes a business process diagram which is based on flowchart techniques, structured to create graphical models of business operations where there are activities and flow controls that define work sequences. The results of the analysis of time on the KK online service business process require a minimum of 34 minutes, a maximum of 42 minutes, an average time of 38 minutes and the total takes 7 hours 24 minutes. Then the time analysis of birth certificates takes a minimum of 30 minutes, a maximum of 46 minutes, an average of 36 minutes 40 seconds and a total of 3 hours 34 minutes. And for a death certificate it takes a minimum of 30 minutes, a maximum of 1 hour 2 minutes, an average of 40 minutes and the whole takes 2 hours 36 minutes.